Failure of ornithine decarboxylase inhibition to alter small intestinal epithelial repair after transient segmental ischaemia. Issue 7 (July 1988) - Guzman, C; MacLeod, R J; Hamilton, J R
Abstract : To evaluate the roles of ornithine decarboxylase (ODC) and polyamines in the regulation of epithelial repair, rabbit mid-small intestine after transient ischaemic villus injury in the presence and absence of DL-difluoromethylornithine (DFMO), an irreversible inhibitor of ODC was studied. Rabbits received 2% (w/v) DFMO in drinking water for two days before undergoing a sham laparotomy, or a 90 minute mesenteric vascular occlusion of 20 cm of mid-intestine. DFMO fed and control rabbits were studied four, 24, 72, or 120 hours after this ischaemic intestinal injury. In controls, ischaemic injury caused shortened villi at four hours (p less than 0.01), diminished mucosal sucrase and alkaline phosphatase activities at 24 hours (p less than 0.05), but raised ODC (p less than 0.001) and thymidine kinase (p less than 0.01) activities at four hours with recovery by 72 hours. DFMO treatment significantly reduced ODC activity at all stages of the experiment and significantly inhibited the rise in activity observed after injury (p less than 0.01). Mucosal concentrations of the polyamines, spermidine and spermine, were similar in the sham operated groups; four hours and 24 hours after ischaemia, they increased in the DFMO animals (p less than 0.01) but fell (p less than 0.05) in those that did not receive DFMO. After ischaemic injury, DFMO treatment inhibited ODC but failed to influence recovery of villus structure or enzyme activities in the small intestine. We conclude that ODC and the polyamines, spermidine and spermine, are not key regulators of small intestinal repair after transient ischaemia.